IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH DI SMAN 1 KERITANG - Yulia Mori Zalni; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Character education is a pillar that builds one of the intelligent and quality Indonesian human characters. Based on observations at SMAN 1 Keritang, the authors show an increase in the implementation of character education that can be taken into account by the school in a planned and planned manner. The purpose of the study was to determine the plan, implementation and evaluation of teachers in the history learning process at SMAN 1 Keritang. Qualitative research method with purposive sampling, data collection techniques include: observation, interviews, documentation and triangulation. The research procedure includes orientation, exploration, and checking the truth of the research results. The results showed that (1) the planning stage of SMAN 1 Keritang was able to arrange teaching materials and school conditions with character education nuances. However, the problem of character education for environmental care values is still found waste that is not sorted even though it has not been provided. The problem of teacher readiness itself, periodically and continuously develoving teacher understanding to be able to provide affective teaching materials and patterns; (2) the implementation stage, the teaching atmosphere formed by the teacher is able to develop critical power and the spirit of cooperation between student. It was found that many students were able to develop their reasoning by studying history teachers; (3) the evaluation stage, the history teacher not only pays attention to the cognitive aspects in assessing students, but also the affective and psychomotor aspects. Where has a significant role in providing an assessment of student abilities. In the addition, for students who are not able to reach the minimum threshold set, the history teacher will conduct teaching and evaluation of students outside hours and emotional scores to find out why students have not achieved the expected value.Key Words: Character Education, History Learning.